2015
DOI: 10.1002/adfm.201502650
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus‐Targeting Gold Nanoclusters for Simultaneous In Vivo Fluorescence Imaging, Gene Delivery, and NIR‐Light Activated Photodynamic Therapy

Abstract: The nucleus is one of the most important cellular organelles and molecular anticancer drugs, such as cisplatin and doxorubicin, that target DNA inside the nucleus, are proving to be more effective at killing cancer cells than those targeting at cytoplasm. Nucleus‐targeting nanomaterials are very rare. It is a grand challenge to design highly efficient nucleus‐targeting multifunctional nanomaterials that are able to perform simultaneous bioimaging and therapy for the destruction of cancer cells. Here, unique nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
142
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(143 citation statements)
references
References 41 publications
0
142
0
Order By: Relevance
“…AuNPs have been extensively used as a core for coating targeting peptides . Lee and co‐workers attached RGD (targets inflammation) to Au half‐shell nanoparticles containing methotrexate (MTX, most widely used RA therapeutic) as an improved photo‐/chemotherapy agent for the treatment of rheumatoid arthritis (RA) in collagen‐induced arthritic (CIA) mice.…”
Section: Peptide‐conjugated Nanomaterialsmentioning
confidence: 99%
“…AuNPs have been extensively used as a core for coating targeting peptides . Lee and co‐workers attached RGD (targets inflammation) to Au half‐shell nanoparticles containing methotrexate (MTX, most widely used RA therapeutic) as an improved photo‐/chemotherapy agent for the treatment of rheumatoid arthritis (RA) in collagen‐induced arthritic (CIA) mice.…”
Section: Peptide‐conjugated Nanomaterialsmentioning
confidence: 99%
“…Vankayala et al reported novel and unique multifunctional gold nanoclusters with nuclear targeting properties. This theranostic nanoplatform was designed to perform simultaneous fluorescence imaging, gene delivery and long (850–1100 nm) NIR light-activated photodynamic therapy for the destruction of cancer cells [98]. The percentage of gene transfection using these multifunctional gold nanoclusters was nearly 3.2-fold higher than that obtained using the most commonly adopted LP2000 liposome gene carrier with NIR light irradiation.…”
Section: Exogenous Stimulus-responsive Nadsmentioning
confidence: 99%
“…Alternative nanostructure hosts containing classical organic PSs have demonstrated improved water solubility and stability; however, most of these methods use nonfunctional polymer-based or silica nanomaterials as carriers, risking the leakage of PS payload from the carriers into the body before reaching their target tumor [11,12]. Nanomaterials, such as TiO 2 [13], tin tungstate nanoparticles [14], ZnO [15], metal nanocluster [16], Cdquantum dots [17], carbon dots [18][19][20], and black phosphorus nanosheets [21], which intrinsically produce 1 O 2 when photoexcited, can overcome these shortcomings. However, concerns regarding biocompatibility and biodegradability of such nanomaterials have hindered their clinical translation.…”
Section: Introductionmentioning
confidence: 99%